Research on Influencing Factors of Fatigue Strength of Wind Turbine Spindles Based on Nonlinear Contact - Song Kewei; Chen Xiaoxu; Liu Xiangyin; Tian Jiabin; Li Xiaoxia (Jixie chuandong)
In order to more reasonably simulate the force and force transmission characteristics of the main shaft of a wind turbine, and to find out the influencing factors of the fatigue strength of the main shaft, the nonlinear contact element is used to simulate the roller of the main bearing and correctly simulate the self-aligning effect of the main bearing. The interference contact model between the main shaft and the inner ring of the main bearing of a wind turbine is established. Based on the equivalent time series load spectrum and Miner's fatigue damage criterion, the effects of the size of the interference between the inner ring of the main shaft and the main-bearing, the size of the inner bore of the spindle, the surface roughness, the friction coefficient of the contact surface and the tensile and yield strength of the material on the fatigue strength properties of the spindle are studied and analyzed. The research results have certain guiding significance for engineering practice and production, and lay a foundation for further lightweight design of spindles.